Autonomous learning and teacher guidance: Towards the improvement of EFL students’ prepared talk in speaking practice - Yusnimar Yusnimar (Studies in English Language and Education, 2019)
This study was aimed to investigate the role of autonomous learning (hereafter, AL) with the teacher guidance approach in enhancing the performance and ability of students in practicing their English speaking skill. Pre-test and post-test were given to 22 first year university students to measure the improvement of their ability in the prepared talk before and after the learning strategy was implemented in the classroom. The questionnaires were also gathered to know their perception of this learning strategy. The questionnaires were in the form of closed-ended questions. Results of the pre-test and post-test were analyzed using Tableau software, meanwhile, the data from the questionnaire were calculated for frequency and percentage. From the results, the average score the students' post-test was higher than the average score they got in the pre-test, 83 and 62.2, respectively. The improvement was obvious; here, 16 students got the scores of 80-95 in their post-test, while others got a minimum of 75 and 60. The students' perception obtained from the questionnaires, in overall, received positive responses on the use of this learning strategy. It can be concluded that AL with the teacher guidance approach played a prominent role in improving the students' performance in English prepared-talk.